POTENSI KOMERSIALISASI JAMUR SUSU (CALOCYBE INDICA) PADA PETANI JAMUR (PENGABDIAN MASYARAKAT DESA PONDOK JERUK-TANGGUL KAB. JEMBER) - Sarah Yuliarini; Titik Inayati; Suharnanik Suharnanik (Universitas YPPI Rembang, 2021)
Calocybe Indica mushroom researches revealed the beneficiary to health such to prevent stroke and breast cancer. Mushroom propagation has not widespread available yet in Indonesia or high bid price than button, clam, wood mushroom. Home farming is based on environmentally and economical method ought to be applied for the calocybe indica propagation. Counselling and training method based on propagation stages are most plausible to bring knowledge about a new high value variety of mushroom. The aim of training for farmers in Pondok Jeruk Vilage, Jember Distric is to bring technical matters using agricultural waste for planting media of Calocybe indica mushroom. Usage of garden and agricultural waste media such as banana leaves, wood grain, and coconut fiber as a differentiator of mushroom cultivation test group, by applying the basic conditions of growing mushrooms in nature. Each group applied similar treatment, then growing mushrooms to be observed intensely up to harvest. Economic assessment is done by looking at the yield of each group. The result of the training is the standard of cultivation of calocybe indica milk mushrooms in Jember district on a home farming scale. The result of the training has invited several mushroom farmers in Jember Regency. They are quite enthusiastic about the training to make mushroom derivative products into sausages, nuggets and seasonings substitute for MSG. The further training related to marketing of the processed mushrooms products, and counselling about initiating to formed a group of farmers mushroom growers. Keywords: Calocybe Indica, Home Farming, Training